A real-world, long-term experience on effectiveness and safety of vedolizumab in adult patients with inflammatory bowel disease: The Cross Pennine study. Issue 12 (December 2018) - Lenti, Marco Vincenzo; Levison, Scott; Eliadou, Elena; Willert, Robert; Kemp, Karen; Carter, Anna; Stansfield, Catherine; Assadsangabi, Arash; Singh, Salil; Crooks, Ben; Tattersall, Suzanne; Fairhurst, Francesca; et al.
Abstract: Background: Real-life data on vedolizumab effectiveness in inflammatory bowel disease (IBD) are still emerging. Data on the comparative safety of the gut selective profile are of particular interest. Aims: To assess clinical outcome and safety in IBD patients treated with vedolizumab. Methods: We retrospectively collected data of patients treated with vedolizumab at eight UK hospitals (August 2014–January 2018). Clinical response and remission at 14 and 52 weeks evaluated through Physician Global Assessment (PGA) and adverse events were recorded. Possible predictors of clinical response were examined. Results: Two hundred and three IBD patients (mean treatment 16 ± 8 months) were included. Of these, 135 patients (mean age 40.6 ± 16.0 years; F:M 1.9:1) had CD and 68 (mean age 44.5 ± 18.1 years; F:M 1:1.2) had UC. According to PGA, 106/135 (78.5%) CD and 62/68 (91.2%) UC patients (p = 0.02) had a clinical response/remission at 14 weeks, whereas 76/119 (63.9%) CD and 52/63 (82.5%) UC patients (p < 0.01) showed a sustained response or remission at 52 weeks, with a high adherence rate (97%). No predictors of clinical response were found. The cumulative incidence of infectious diseases was 11.9 per 100 person-years. Conclusion: Vedolizumab is an effective therapy for inducing and maintaining remission of IBD, with better results for UC, and with a good safety profile.